Rotation Estimation of Acoustic Camera Based on Illuminated Area in Acoustic Image. Issue 21 (2019) - Wang, Yusheng; Ji, Yonghoon; Woo, Hanwool; Tamura, Yusuke; Tsuchiya, Hiroshi; Yamashita, Atsushi; Asama, Hajime
Abstract: In this paper, the concept of illuminated area, an important characteristic in acoustic images, is formalized, which can be applied to tasks such as the 3D mapping of underwater environment. Unmanned exploration using underwater robots is gaining attention among the scientific community. A way to sense the underwater environment is to employ the acoustic camera, a next generation forward looking sonar with high resolution even in turbid water. It is more flexible than common underwater sonars; however, studies on acoustic cameras are still at the early stage. Acoustic cameras have a fixed vertical beam width able to generate a limited bright area on acoustic images which is named illuminated area. In this paper, we propose the concept of illuminated area and the method to detect the illuminated area under a flatness assumption of the ground. Then, it is shown how the knowledge of the illuminated area can be fused with depth information to estimate the roll and pitch angles of the acoustic camera. The estimated quantities can be employed to carry out a 3D mapping process. Experiment shows the validity and effectiveness of the proposed method.